2014
DOI: 10.3109/10717544.2014.902146
|View full text |Cite
|
Sign up to set email alerts
|

Novel carbopol-based transfersomal gel of 5-fluorouracil for skin cancer treatment:in vitrocharacterization andin vivostudy

Abstract: 5-fluorouracil (5-Fu) is an antineoplastic drug, topically used for the treatment of actinic keratosis and nonmelanoma skin cancer. It shows poor percutaneous permeation through the conventionally applicable creams and thus inefficient for the treatment of deep-seated skin cancer. In the present article, transfersomal gel containing 5-Fu was investigated for the treatment of skin cancer. Different formulation of tranfersomes was prepared using Tween-80 and Span-80 as edge activators. The vesicles were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(50 citation statements)
references
References 27 publications
2
47
0
1
Order By: Relevance
“…Our results agreed with previous studies demonstrated the effect of the HLB of surfactant on the particle size of drugloaded transfersomes (Abdelbary & El-Gendy, 2008;Khan et al, 2014;Ali et al, 2015), which all encapsulate watersoluble drugs. But disagree with other studies incorporating water insoluble drugs (Yusuf et al, 2014;Aboud et al, 2015).…”
Section: Particle Size and Pdisupporting
confidence: 93%
“…Our results agreed with previous studies demonstrated the effect of the HLB of surfactant on the particle size of drugloaded transfersomes (Abdelbary & El-Gendy, 2008;Khan et al, 2014;Ali et al, 2015), which all encapsulate watersoluble drugs. But disagree with other studies incorporating water insoluble drugs (Yusuf et al, 2014;Aboud et al, 2015).…”
Section: Particle Size and Pdisupporting
confidence: 93%
“…Several colloidal formulations containing 5-FU (niosomes, ultradeformable liposomes, and so on) for skin application have been developed and their in vivo potential has been explored. [20][21][22] Therefore, the aim of this study was to design and characterize an 5-FU-loaded NLC (5-FU-NLC) as potential carrier for the topical delivery of 5-FU. The optimized 5-FU-NLC batches were dispersed in 1% Carbopol ® 934 (poly[acrylic acid]) gel to achieve increased contact time and get the semisolid consistency suitable for topical application.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer dispersions, such as hydrogels, have been studied intensively for skin bioadhesion in topical cutaneous drug delivery, [70][71][72][73][74][75][76][77] and showed good results for bioadhesion.…”
mentioning
confidence: 99%